Metal Fabricating Process by Powder Metallurgy - D.N. Adnyana (Journal of Mathematical and Fundamental Sciences, 1979)
Abstract. The aim of this introductory paper is to consider some of the important principles that are commonly involved in the field of powder metallurgy. These principles cover a general description of the interrelations of the various effects in the powder metallurgy such as characterization of powders, compaction and sintering. Their influences on all process routes are described and their pertinent relations to the experimental results are discussed. Sari. Maksud dari tulisan ini adalah untuk memberikan pengarahan dengan memperhatikan beberapa prinsip-prinsip dasar penting yang biasanya dikaitkan dengan bidang puder metallurgi(+). Prinsip-prinsip ini meliputin suatu uraian umum dari hubungan-hubungan untuk bermacam-macam pengaruh di dalam puder metallurgi, seperti: peranan dan sifat-sifat puder, proses-proses pengepresan dan penyinteran. Suatu uraian dan diskusi diberikan mengenai pengaruh-pengaruh itu terhadap semua jalnnya proses dan kemudian dihubungkan dengan hasil-hasil eksperimen yang diperoleh.